Sexual dimorphism of Colorado beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) in the west and northwest of Iran by geometric morphometric method - Rahim Abdolahi Mesbah; Jamasb Nozari (تاکسونومی و بیوسیستماتیک, 2014)
The males and females of Colorado beetles do not reveal clear dimorphism and therefore they have high resemblance so that recognition of the sexes by simple eye is too difficult. In order to study sexual dimorphism in Colorado beetle, three geographical populations were collected from potato fields in Ardabil, Bahar and Hamedan regions by manual method and direct observation in the summer of 2012. Fore and hind wings were separated and 7 and 8 landmarks were orderly selected for the fore and hind wings at the end and angle of veins. Geometric coordinate of landmarks were converted to shape and size variables as comparison factors between the sexes. Wings relative variations were determined separately in male and female and it revealed variations of wing shape in evolutionary process. Multivariate analysis based on the results of regression of shape variables showed fore wing had allometry and hind wing had not allometry. Two way MANOVA analysis was conducted for observation of shape differences (base on average of shape variables) and size differences. The analysis showed that there were significant differences in shape of fore wing between the sexes.